Nowhere Nation - Ashok Mitra
An unbiased critique of the Indian State from an insider Forcefully argued, elegantly written reflections first that appeared in The Telegraph The author is a widely read and followed columnist Questioning the image of India as a nascent superpower or putative economic powerhouse that has been the flavour of the decade, Ashok Mitra draws on his experience as India s chief economic adviser and West Bengal s finance minister to look at critical current issues that include the policies of liberalization, the Indo US nuclear deal and the attempt to take away land from peasants for industrialization. His clear sighted analyses of the roots of such societal tendencies as communalism and corruption force us to reexamine our assumptions about contemporary Indian realities and, indeed, question if there is a single Indian reality at all. The Nowhere Nation argues that India embraces several historical ages at a single point of time. Three-quarters of Indian citizens are horrendously poor; of which at least a quarter is below the level of subsistence. The rest do well, some very well indeed. But how does this all work? India, writes Mitra, simmers in its incongruities . The classes, castes and communities live their parallel lives and sort out their own economics. Reforms will not pry open up the exclusive saloon the Indian superstructure is accustomed to claim; and the usual trickle-down defence ignores the difficult truth that jobs do not grow in the short run; in fact they shrink. Furthermore, the West Bengal experiment has proved that even when the opportunities are available to attempt social and economic restructuring in a miniature frame, contamination seeps in.